Polygamy in Islam: A Study on Its Religious Justifications and Empowerment of Women Within Islamic Teachings - Sereikaite Motiejune, Gintare (Universitas Muhammadiyah Surakarta, 2025)
This research article delves into the intricate dynamics of polygamy in Islam, emphasizing its potential as a support system among co-wives. Traditionally viewed with controversy, especially in Western societies, this study challenges such perceptions by highlighting how polygamous arrangements can foster mutual support, shared responsibilities, and companionship. By examining these relationships through religious, cultural, and social lenses, the study reveals how polygamy can empower women within the framework of Islamic teachings, transforming traditional familial roles and enhancing their agency. Women's choices to enter polygamous marriages often reflect a complex interplay of factors, combining strategic decision-making for financial or social stability with deeply rooted religious motivations and commitments. The research utilizes diverse narratives from a global Facebook group, allowing for a comprehensive exploration of polygamy's dynamics and benefits. This perspective underscores polygamy's role as a supportive alliance among women, contributing significantly to broader discussions on gender dynamics and marital structures within both Islamic and global contexts.